2004
DOI: 10.1007/bf02481674
|View full text |Cite
|
Sign up to set email alerts
|

Towards a prediction of superplasticized concrete rheology

Abstract: The rheology of concrete is influenced by water content, the amount, size and size distribution of all the solid components as well as by the dispersion of the finer particles through the addition of superplasticizers. In addition, the rheological behaviour over time evolves as a result of cement hydration. Consequently the a-priori prediction of concrete rheology is a complex task.In this article, models that have been and are being developed to achieve this task are discussed. The key role of the degree of d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
36
0
2

Year Published

2005
2005
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 127 publications
(40 citation statements)
references
References 21 publications
(35 reference statements)
2
36
0
2
Order By: Relevance
“…Several types of non-contact interactions occurred within a cementitious suspension [21]. The mechanism for PCE in a cement-water system mainly included electrostatic repulsion, steric hindrance and lubrication [22,23,24].…”
Section: Resultsmentioning
confidence: 99%
“…Several types of non-contact interactions occurred within a cementitious suspension [21]. The mechanism for PCE in a cement-water system mainly included electrostatic repulsion, steric hindrance and lubrication [22,23,24].…”
Section: Resultsmentioning
confidence: 99%
“…For such materials, some authors have linked the yield stress to the material solid volume fraction (Flatt,[26]; Legrand [27]; Chateau [28]; Ildefonce et al [29]). Due to liquid filtration during extrusion, the material solid volume fraction is expected to evolve in the extruder.…”
Section: Rheological Behaviourmentioning
confidence: 99%
“…Other quoted models can be used [26][27][28][29]. The Legrand model has been used in this case for its simplicity.…”
Section: Rheological Behaviourmentioning
confidence: 99%
“…The addition of HRWRA for mix C11, C12, and C13 resulted in decreases in the yield values measured by both the ICAR rheometer and the truck. Many authors [18,19,20] have shown that concrete slump is inversely correlated to yield stress, because a high slump indicates a reduced resistance to flow as does a low yield stress. Indeed, the slump increased as the truck measurements and ICAR rheometer indicated a reduction in yield stress due to the addition of HRWRA.…”
Section: Resultsmentioning
confidence: 99%